Slow-sinking particulate organic carbon and its attenuation in the mesopelagic water of the South China Sea - Yang, Weifeng; Zhao, Xiufeng; Zheng, Minfang (Frontiers in Marine Science, 2022)
Coastal acidification has been widely investigated in terms of its rationale and ecological effects in the last decade. However, the driving mechanism for acidification in open seawater, especially in mesopelagic water, is still poorly understood. Here, the sinking velocity and flux attenuation of particulate organic carbon (POC) were examined based upon the radioactive 210Po-210Pb tracer to reveal the remineralization of POC in the mesopelagic zone in the northeastern South China Sea (SCS). Overall, the profiles of 210Po followed those of 210Pb, lending support to the particle sinking controlled top-down deficits of 210Po. Using an inverse model, the sinking velocity of particles, for the first time in the SCS, was estimated to vary from 3 to 34 m d-1 with the mean value of 15 ± 9 m d-1, indicating that the slow sinking particles largely contribute to the POC flux in the SCS. Beneath the euphotic zone, a consistent descending of the sinking speed implied continuous remineralization of sinking POC in the twilight zone. A preliminary estimate revealed that 1.9-5.4 mmol-C m-2 d-1 remineralized back to carbon dioxide within 100-500 m, representing about 70% of the exported autochthonous POC from the euphotic zone. In 100-1000 m, 2.4-6.6 mmol-C m-2 d-1 (i.e., 84%) remineralized. Thus, the upper twilight zone (i.e., 100-500 m) is the dominant layer of POC remineralization, and POC-induced acidification could be unneglectable there. These results provided insights into the POC-induced acidification mechanism in the mesopelagic water, especially in the upper mesopelagic layer.